Genetic and environmental influences on fatty acid and tocopherol diversity in quinoa germplasm - Velasco, Leonardo; Matías, Javier; Cruz, Verónica; Fondevilla, Sara (Frontiers in Plant Science, 2025)
IntroductionQuinoa (Chenopodium quinoa Willd.) is a food crop highly valued for being nutritious and health-promoting. As quinoa grains contain more oil than cereals, the fatty acid profile is an important nutritional criterion. The tocopherol family, with vitamin E and anti-inflammatory properties, are also relevant compounds for the nutritional quality of quinoa. Currently, information on the genetic diversity of these compounds in quinoa germplasm is limited.MethodsFatty acid and tocopherol contents and profiles were analyzed, using gas chromatography and HPLC, respectively, in the seeds of 126 quinoa accessions from diverse origins grown in two locations in Spain in 2021 and 2022, following a completely randomised block design with three replications.ResultsThe germplasm exhibited a wide diversity for all the traits analysed, showing contrasting contents and profiles of fatty acids and tocopherols. Considering the data averaged over the four environments, particularly relevant variation was observed for total fatty acid, from 1.0 to 4.4% of grain weight; oleic acid, from 13.4 to 32.3% of total fatty acids; linoleic acid, from 48.0 to 67.4%; linolenic acid, from 1.8 to 8.4%; tocopherol content, from 22.3 to 121.6 mg kg-1 grain; α-tocopherol, from 24.6 to 81.4% of the total tocopherols; and γ-tocopherol, from, 18.6 to 75.4%. Broad-sense heritability (H2) was found to be high for linolenic acid content (0.86) and the concentrations of α- and γ-tocopherol (0.84). For most of the other traits, H2 ranged from 0.65 to 0.77. Principal component analysis successfully separated highland accessions from Bolivia and Peru and lowland accessions from Chile and the USA.DiscussionThe existence of wide genetic diversity for grain oil content, fatty acid profile, and tocopherol content and profile in quinoa germplasm, together with the medium to high heritability of these traits, suggests the feasibility of improving these characters through breeding.